IMPLEMENTASI PROGRAM ADIWIYATA BERBASIS NILAI-NILAI ISLAM DALAM MENINGKATKAN KESADARAN LINGKUNGAN DI KALANGAN SISWA (STUDI KASUS SMP NEGERI 1 PARDASUKA) - Khoirut Tobib, Ahmad Syafak; Rahma Putri, Dwi Suci; Khansa, Elsa Al; Murtadho, Ali; Baharudin, Baharudin; Mustofa, Ikhsan (Raudhah - Proud To Be Professional, 2024)
This study aims to analyze the implementation of the Adiwiyata Program in increasing environmental awareness among students at SMP Negeri 1 Pardasuka. The Adiwiyata Program, which focuses on waste management, greening, and energy efficiency, aims to form an environmentally conscious character through education that integrates environmental values ??into the curriculum. This study uses a qualitative approach with a case study type, where data is collected through interviews, observations, and documentation involving the principal, teachers, and students. Data analysis was carried out using data reduction, data presentation, and conclusion drawing methods. The results of the study indicate that despite challenges in terms of school commitment and active student participation, the Adiwiyata Program has succeeded in increasing students' environmental awareness, especially in waste management and greening. This study is expected to provide recommendations to optimize program implementation, as well as support the development of environmental education that is in line with Islamic teachings on preserving nature as part of worship to Allah SWT.